Strategies for managing diseases in non‐native shrimp populations - James Cock; Marcela Salazar; Morten Rye (Reviews in Aquaculture, 2017)
The shrimp industry is now largely based on Litopenaeus vannamei . Current strategies for disease management in Asia emphasizing exclusion and eradication with strict quarantine and importation protocols have not been effective in controlling disease epidemics. New diseases have been introduced on illegal importations; commercial shrimp populations are derived from imported SPF stocks susceptible to endemic diseases; and local breeding programmes are based on populations not resistant to a range of diseases. Broodstock are largely poorly adapted to local conditions and repeated disease epidemics occur. Strategies for disease management should concentrate on: (i) minimizing the risk of introducing new diseases to the region; (ii) development of populations more resistant to endemic diseases; and (iii) better management practices that minimize the likelihood of serious epidemics and delay infection, but do not depend on attempts to eradicate diseases already present. This can be implemented by building on the better management practices already established in the region and in addition: (i) applying strict quarantine procedures for diseases not reported in the region whilst making the processes sufficiently agile to reduce illegal introductions; (ii) eliminating standard rigid importation protocols and tailoring protocols in accordance with the disease situation of both the country of origin and destination; (iii) increasing genetic variation available within Asia by public sector support for programmes to enlarge the pool of genetic variation and encouraging collaboration with breeding programmes that encompass a broad genetic base; (iv) establishing selection programmes that permit reincorporation of animals exposed to disease into the breeding nucleus; and (v) establishing propagation systems that provide growers with high health status stocks without requiring overly strict SPF certification of facilities.